Toxonomic novelties in south brazilian amaryllidaceae-I: Hippeastrum ramboi new species from Rio Grande do sul and lectotypification of H. Breviflorum herb - Büneker, Henrique Mallmann; Bastianabral, Regis Eduardo (Balduinia, 2017)
Hippeastrum ramboi, a new species of Amaryllidaceae (Amaryllidoideae, Hippeastreae) endemic to the mountainous region of Rio Grande do Sul (Brazil) is described and illustrated. Data one its habitat, cology, geographic distribution is provided and its threat status is evaluated according to IUCN criteria. The new species has morphological affinity with H. sanctaecatharinae and H. breviflorum, the last one has not been correctly typified up to date, being lectotyped here to correctly define the circumscription of this taxonomic entity in comparison to the new species.